2018
DOI: 10.1038/s41598-018-32553-5
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 from Flaxseed Oil Protects Obese Mice Against Diabetic Retinopathy Through GPR120 Receptor

Abstract: The chronic and low-grade inflammation induced by obesity seem to be the “first hit” to retinopathy associated to diabetes type 2. Herein, we hypothesized that omega-3 fatty acids from flaxseed oil enriched diet disrupt the pro-inflammatory status in the retina, protecting against retinopathy development. For eight weeks under a high-fat diet (HF), several physiological parameters were monitored to follow the metabolic homeostasis disruption. After this period, mice were treated with a HF substituted in part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
2
23
1
1
Order By: Relevance
“…omega-3 fatty acids [39], which mitigate the inflammatory reactions and reduce the risk of cardiovascular diseases [40]. Moreover, other polyunsaturated fatty acids (PUFAs), present in flaxseeds, may protect the retina from harmful effects of diabetes mellitus type 2 [41]. Flaxseeds also possess lignans, which act as antioxidant due to their ability of scavenging free radicals [42].…”
Section: Introductionmentioning
confidence: 99%
“…omega-3 fatty acids [39], which mitigate the inflammatory reactions and reduce the risk of cardiovascular diseases [40]. Moreover, other polyunsaturated fatty acids (PUFAs), present in flaxseeds, may protect the retina from harmful effects of diabetes mellitus type 2 [41]. Flaxseeds also possess lignans, which act as antioxidant due to their ability of scavenging free radicals [42].…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma, RP and DR [119][120][121][122] Spermidine Acts as a ROS scavenger by sequestering singlet oxygen and reactive species and reduced RGC death. Glaucoma [123] Lycopene Decreases NF-κB activation and ROS production in RPE cells, while increasing Nrf2 and GSH levels.…”
Section: Zinc and Manganesementioning
confidence: 99%
“…In another study, using a different mouse strain, the Swiss mice fed HFD for 8 weeks was shown to be sufficient to induce an increased body weight, increased fasting glucose, decreased insulin tolerance, and decreased OP (but without differences among amplitudes of wave a, b, or c, which are responsive for cones, rods, and epithelial cells, respectively). However, after 16 weeks, HFD induced a pro-inflammatory state in the retinal tissue (increased tumor necrosis factor (TNF)-α and interleukin 1 beta (IL-1β) gene expression and protein levels) and significantly increased levels of the inducer of VEGF that regulates angiogenesis by inducing proliferation of retinal endothelial cells and enhances vascular permeability [61]. A rodent model using HFD combined with STZ injection (single injection of high dose or multiple injections of low dose) to induce chronic hyperglycemia is the most widely accepted animal model for studying retinal complications in T2DM [8,62,64].…”
Section: Diet-induced Models Of Diabetic Retinopathymentioning
confidence: 99%